Pengembangan Media Interaktif berbasis Mobile pada Mata Pelajaran Pendidikan Pancasila di SMKS Veteran 1 Tulungagung - Mokhammad Nur Kafi; Nurna Listya Purnamasari (Universitas Nusantara PGRI Kediri, 2024)
This study aims to evaluate the feasibility of developing mobile-based interactive media in Pancasila Education subjects. The procedure used is research and development with the ADDIE method. The product produced in this study is a mobile-based learning media that includes Bhinneka Tunggal Ika material with local wisdom. The feasibility test obtained a score of 94% from media experts and 95% from material experts, while the evaluation stage involved small group trials with a score of 86% and large group trials with a score of 93%. Based on these results, it can be concluded that the developed mobile-based interactive learning media is very feasible to use in the learning process, showing great potential in increasing the effectiveness of education and the relevance of the application of mobile technology in the educational environment.